Unravelling the genetic basis of banana traits using next generation sequencing technologies - Bioversity International (Bioversity International, 2015)
The availability of the banana reference genome sequence (D’Hont et al., 2012) and Next Generation Sequencing technologies have boosted research that helps to better understand the banana (Musa spp.) genetic diversity held in the Bioversity International Musa Germplasm Transit Centre (ITC). New insights into the genetics of the crop, associated with phenotyping, enable the exploration of banana genetic resources for a range of important end-users’ traits, to support further uses to enhance food and nutritional security. We are taking advantage of the latest Next Generation Sequencing technologies to i) produce high-density genetic markers for a large number of samples at low cost, and ii) to sequence, assemble and annotate key genomes, thus generating an unprecedented volume of information for researchers and breeders. Using the deluge of genomics data creates both a challenge and an opportunity. It places a unique challenge upon bio-informaticians to deal with the volume, speed and variety of data generated and to provide adequate storage, analyses and graphic visualization. At the same time, it provides a unique opportunity to unlock the potential of the genetic diversity stored in genebanks.